Outcome and Severity of COVID-19 in Vaccinated and Unvaccinated patients - Syeda Naveera Raza, Santosh Kumar, Ambrina Khatoon, Nida Hussain, Urfa Kayani (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The coronavirus disease of 2019 (COVID-19) pandemic is the world’s worst problem and the global health disaster of our time. In order to fully comprehend the advantages of COVID-19 immunization, illness attenuation must be considered. This should be done by investigating whether those who contract COVID-19 despite vaccination experience milder symptoms than those who are unvaccinated. The COVID-19 pandemic brought on by is still a serious public health issue on a global scale. Aim: To evaluate the significant impact and efficacy of vaccination in positive SARS-CoV-2 patients during different timelines of a pandemic. Methodology: This is a cross sectional study involving 212 PCR-positive SARS-CoV-2 patients with their clinical–epidemiological findings admitted at Ziauddin Hospital between the years 2021 to 2022. SARS-CoV-2. RNA positivity was determined using qualitative RT-PCR with in vitro diagnostic kits, following the manufacturer’s recommendations. SARS-CoV-2 positive patients had at least one positive RT-PCR test result, while SARS-CoV-2 negative patients had solely negative RT-PCR test findings. The data was provided through electronic patient records. The patients were categorized into Asymptomatic, Mild, Moderate and Severe/Critical as per WHO and CDC guidelines. Results: Among total of 212 patients there were 5(2.4%) vaccinated and 20(9.4%) unvaccinated asymptomatic, 6(2.8%) vaccinated and 12(5.7%) unvaccinated mild, 16(7.5%) vaccinated and 39(18.4%) unvaccinated moderate and 27(12.7%) vaccinated and 87(41%) unvaccinated severely/critically ill patients. The association between the severity of illness and vaccination status of patients showed significantly positive results with a p-value of 0.005. Conclusion: It was concluded that vaccine plays a significant role in the course of illness and severity of disease, this study investigated the impact of vaccination status on patients with positive SARS-CoV-2 to compare the severity and course of illness between the vaccinated and unvaccinated groups based on a number of clinical indicators. but the efficacy of these vaccines remains a point of concern for future studies. Key words: COVID-19, pneumonia, SARS-CoV-2, immunization